Comparative Analysis of 2-Point Jump Shot and Free Throw Kinematics in High- and Low-Level U18 Male Basketball Players - Varvara Botsi; Dimitrios I. Bourdas; Antonios K. Travlos; Panteleimon Bakirtzoglou; Dimitrios C. Gofas; Ioannis E. Ktistakis; Emmanouil Zacharakis (Journal of Functional Morphology and Kinesiology)
Background/Objectives: This study examined the influence of competition level and player position on shooting accuracy and kinematic parameters in U18 male basketball players, focusing on two-point jump shots and free throws. Methods: Thirty-eight higher-level (HL-group) and forty-one lower-level (LL-group) participants, categorized into guard, forward, and center subgroups, completed a two-point basketball shooting test, followed by a free-throw shooting test after a 30 min interval. These tests were administered using a crossover, counterbalanced approach with the Latin square method to ensure effective randomization. Results: The results indicated that the HL group displayed significantly faster (12.5%) shot release times (RTs) and closer-to-optimal 45° (8.1%) ball entry angles (EAs) into the hoop for free throws, as well as superior (24.2%) shot success rates (SSRs) for two-point jump shots compared with the LL group. Across all groups and subgroups, a higher EA was achieved in two-point shots than in free throws, though free throws showed higher SSR. This study found no positional differences in shooting mechanics or performance, suggesting that modern training practices may foster consistency across player roles. Conclusions: These findings emphasize the potential for targeted drills to improve RTs, EAs, and SSRs, especially in LL players. Coaches can apply these insights to enhance shooting mechanics and consistency, thereby elevating performance in young basketball athletes. Future research should investigate the impact of fatigue and defensive pressure on shooting parameters across varied competitive contexts.